A Guideline of Ultrasonic Inspection on Butt Welded Plates - Burhan I.; Mutaiyah G.; Hashim D.I.; Loganathan T.M.; Sultan M.T.H. (Institute of Physics Publishing, 2023)
Butt welding; Defects; Inspection; Nondestructive examination; Welded steel structures; X ray films; X ray radiography; Double v; Mathematical formulas; Radiographic films; Radiographic inspection; Stand-off; Ultrasonic inspections; Ultrasonic techniques; Welded plates; Ultrasonic testing